Case Report: Novel UNC93B1 variant causes rheumatoid arthritis and interstitial pneumonia - He, Tingyan; Ou, Junbin; Huang, Lijuan; Zhou, Xinyi; Wang, Linlin; Li, Xiaolin; Yang, Jun (Frontiers in Immunology, 2025)
BackgroundUNC93B1 is a transmembrane protein essential for regulating toll-like receptors (TLRs). Pathogenic variants in human UNC93B1 have recently been described in a limited number of patients with childhood systemic lupus erythematosus and chilblain lupus.MethodsDemographic data, medical history, and physical examination findings were obtained. Whole-exome sequencing and Sanger sequencing were performed. The interferon-stimulated gene (ISG) score was analyzed.ResultsWe report four patients with a novel UNC93B1 c.1007G>A p.R336H variant, including three presenting with juvenile arthritis or rheumatoid arthritis, and one with a predominant phenotype of ITP. In addition to arthritis, these patients presented with interstitial pneumonia as the dominant feature. ISG expression analysis during active disease revealed overexpression of IFN-stimulated cytokine genes and an elevated ISG score in P4. To date, 25 cases with UNC93B1 pathogenic mutations have been reported, including 13 with childhood-onset systemic lupus erythematosus (SLE) and 12 with cutaneous lupus. Management of these patients has varied based on clinical manifestations.ConclusionUNC93B1-mutation-associated disease should be considered in the context of early-onset autoimmune disease, especially childhood-onset SLE, juvenile arthritis, and rheumatoid arthritis. Pulmonary involvement should also be monitored in these patients.